2023
DOI: 10.1111/iwj.14350
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of surgical site infection and risk factors in patients after foot and ankle surgery: A systematic review and meta‐analysis

Jiaguo Cheng,
Luping Zhang,
Jing Zhang
et al.

Abstract: The present systematic review and meta‐analysis aimed to determine the prevalence of surgical site infection (SSI) and related factors in patients after foot and ankle surgery. A comprehensive, systematic search was conducted in different international electronic databases, such as Scopus, PubMed, Web of Science and Persian electronic databases such as Iranmedex and Scientific Information Database (SID) using keywords extracted from Medical Subject Headings such as ‘Prevalence’, ‘Surgical wound infection’, ‘Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A systematic review and meta‐analysis revealed that 4.2% of patients who underwent foot and ankle surgery experienced SSI. 3 The findings from another systematic review and meta‐analysis revealed that the occurrence of SSI among patients following long bone surgery is 3.3%. 11 The variance in the prevalence of orthopaedic SSI between our study and these previous investigations can be attributed to the differences in surgical site locations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review and meta‐analysis revealed that 4.2% of patients who underwent foot and ankle surgery experienced SSI. 3 The findings from another systematic review and meta‐analysis revealed that the occurrence of SSI among patients following long bone surgery is 3.3%. 11 The variance in the prevalence of orthopaedic SSI between our study and these previous investigations can be attributed to the differences in surgical site locations.…”
Section: Discussionmentioning
confidence: 99%
“…In orthopaedic surgery, a surgical site infection (SSI) is characterized as an infection that develops within 30 days following surgery when no fixation devices have been implanted, or within 1 year if a metallic device remains implanted. 1 , 2 , 3 , 4 SSI represents a prevalent complication in both orthopaedic and various other surgical procedures. The elevated incidence of SSI can be attributed to factors such as the expanding range of orthopaedic indications, the intricate nature of orthopaedic surgeries and the frequent use of implants in these procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An a priori sample size calculation regarding our secondary outcome, SSI rate, was performed using α = 0.05 and 80% power to detect a doubling of the expected 4% SSI rate reported in the literature for foot and ankle surgery. 4 This resulted in a sample size of 1106. Because the surgical site preparation remained the same for both protocols, the decision was made to base our sample size solely on our primary outcome.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Diabetes patients are prone to incision infection, and many literature reports that pancreatic-dependent and noninsulin pancreatic-dependent diabetes patients will increase the risk of incision infection. 4 Therefore, some studies have found that optimizing blood sugar levels can reduce the incidence of surgical incision infections. 5 Second, the surgical time is not given in Table 1.…”
mentioning
confidence: 99%